Herbicides, glyphosate resistance and acute mammalian toxicity: Simulating an environmental effect of glyphosate-resistant weeds in the USA - Gardner, J.; Nelson, Gerald C. (Wiley, 2008)
BACKGROUND: With the emergence of glyphosate‐resistant (GR) weeds, the environmental consequences of alternatives to GR technology are of increasing importance. A well‐known acute mammalian toxicity measure, the LD50 dose for rats, is used to assess one potential environmental impact of the loss of GR technology. A new dataset with this index is used to estimate and simulate the effects for corn, soybeans and cotton.RESULTS: With conventional tillage it is found that the use of GR seeds reduces the number of LD50 doses applied per hectare by 17–98% depending on crop. With no‐till, the use of GR seeds reduces LD50 doses only in corn. If farmers switch to conventional seeds because of GR weeds but maintain the same tillage practice, the present simulations suggest that LD50 doses could increase by as much as 100 LD50 doses per hectare in soybeans, and 500 LD50 doses per hectare in cotton, or 11.4 and 19.8% respectively.CONCLUSIONS: This is the first study to use field‐level data to assess GR technology with a mammalian toxicity environmental indicator. It has been found that GR crops have a positive environmental effect, and that alternatives to GR technology increase toxicity. Copyright © 2007 Society of Chemical Industry